Podróże z Hanną Szumańską-Grossową - Tokarska-Bakir, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
This paper discusses Podróże Stefana Szolca Rogozińskiego (The Journeys of Stefan Szolc Rogoziński) from 1967 by Hanna Szumańska-Grossowa, against the background of the interests in her time.